The effect of intergroup contact toward social stigma towards survivors of COVID-19: Pengaruh intergroup contact terhadap stigma sosial pada penyintas COVID-19 - Siregar, Mastiur Imelda; Purba, Ridhoi Meilona (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
This study examines the effect of intergroup contact on social stigma among survivors of COVID-19. Participants were 25 people recruited incidentally. We assigned participants to communicate via a video conference platform with survivors of COVID-19 to induce contact. We measured participants' stigma towards survivors of COVID-19 before and after the contact treatment. There was no significant reduction of stigma after the video conference contact. Penelitian ini mengkaji pengaruh kontak antar kelompok terhadap stigma sosial di kalangan penyintas COVID-19. Partisipan berjumlah 25 orang yang direkrut secara incidental. Kami menugaskan peserta untuk berkomunikasi melalui platform konferensi video dengan para penyintas COVID-19 untuk mendorong kontak. Kami mengukur stigma peserta terhadap penyintas COVID-19 sebelum dan sesudah treatment kontak. Tidak ada pengurangan stigma yang signifikan setelah partisipan melakukan kontak melalui konferensi video.